The relationships of character strengths with job stress, mental wellbeing and perceived stress among financial professionals - Kutebayev, Talgat; Lloyd, Robert L. (Frontiers in Psychology, 2025)
IntroductionCharacter strengths have been related to job stress, mental wellbeing and perceived stress, however, little is known about these associations among financial professionals. The aim of this study was to investigate the relationships between character strengths, job stress, mental wellbeing and perceived stress in this occupational group.MethodsData were collected from 523 financial professionals in Kazakhstan using the Job Stress Survey, Values in Action Inventory of Strengths-Virtues 6, Short Warwick-Edinburgh Mental Wellbeing Scale and Perceived Stress Scale.ResultsRegression analysis revealed that interpersonal strengths negatively predicted job stress, while intellectual strengths positively predicted job stress. Results showed that emotional, interpersonal and theological strengths positively predicted mental wellbeing, with theological strengths as the strongest predictor. The study also found that emotional, restraint and theological strengths negatively predicted perceived stress, and emotional strengths were revealed as the strongest predictor.ConclusionThe findings provide novel insights for organizations to develop preventive interventions based on character strengths for effective stress management, particularly perceived stress, and enhancing mental wellbeing.